ANALYZING OF THE PROGOS; STUDENTS' PERSPECTIVE OF IMPROVING ENGLISH SPEAKING SKILL - Aulia, Sirrul; Hz, Benni Ichsanda Rahman (Universitas PGRI Sumatera Barat, 2025)
This study looked at the benefits of using Progos from students Perspective, Progos an AI-based tool, to help students improve their speaking skills. Students in their final year of English and non-English majors at several universities in Medan. This research, which used a qualitative case study technique, assessed data obtained through questionnaires, interviews with students, and post-test findings to compare the initial and final usage. The findings showed that Progos is a successful AI-based tool to improve students' speaking skills by assisting students in understanding the context of speech, expanding vocabulary, improving grammatical accuracy, and increasing confidence in speaking. The study also investigated the advantages of using the Progos app for speaking in addition to the Interview simulation tool in language learning and made recommendations for students. Who desire to include technology into their speaking practice.